(untitled) (Research, Society and Development, 2020)
This text consists of a test that crosses the paths of two education professionals who are in the Graduate Program in Education at the doctoral level / PPGE / UFMT, in the course of Teaching discipline in higher education, and are in their trajectories the rationale for their research intentions. With fulcrum in the frame of teacher professional development, decided to write together, their stories. It is important to consider that the reflections that make sense in this text take shape from the interweaving of life stories, of their research paths and recognition of research and training space. The text of the life stories of the researchers, seeks to raise the reflective elements in search paths, revealing the points that are formative aspects of construction. Thus, this essay seeks to evoke from the stories that were not born teachers, we become teachers over a lifetime.